Rock art, myth and sacred landscapes: the case of a rock art site in Tororo District, Uganda - Namono, C. (Southern African Humanities, 2008)
A rock art site located in Tororo District, eastern Uganda has become a shrine. The shrine derives from beliefs Bantu-speaking ethnic groups have, but belongs to a Western Nilotic-speaking people. A myth about the emergence of the shrine attempts to rationalize its occupation by the present Nilotic-speaking people. This paper considers how myth asserts a sense of identity in a place marked in ancient times as a site for ritual and has now taken on an extended life as a shrine. To cite this article: Namono, C. 2008. Rock art, myth and sacred landscapes: the case of a rock art site in Tororo District, Uganda. Southern African Humanities20: 317-31.